Ocular Manifestations of Meningitis in Children - Chaudhary, M; Shah, DN; Sharma, PR (Journal of Nepal Paediatric Society, 2012)
Introduction: Meningitis is the most common central nervous system disease affecting children leading to focal neurological deficits and various oculovisual anomalies including blindness in children. The objective of this study was to evaluate the oculovisual anomalies occurring in Nepalese children suffering from different types of bacterial meningitis. Materials and Methods: A Prospective, study was undertaken for 18 months at B.P.Koirala Lion’s Center for ophthalmic studies, TU Teaching Hospital to study the children suffering from bacterial meningitis admitted at Kanti Children’s Hospital for ocular involvement. A through history, anterior and posterior segment ocular examination and investigations like blood, CSF and CT scan were done. Results: A total of 182 cases of bacterial meningitis were screened. Tubercular meningitis cases were 40 (21.97%) and Pyogenic were 142 (78.02%). Oculovisual anomalies were seen in 70 (38.46%) cases. The ocular abnormalities included pupillary changes (34.28%), Cranial Nerve Palsy (22.86%), Fundus changes (35.72%), Cortical Blindness (4.28%), Panophthalmitis and Proptosis (1.43%). Third nerve involvement was seen in 17.14% cases, sixth nerve in 4.29% cases, Papilledema in 11.43 % and Optic atrophy in 22.86 %. Risk factors included late presentation; hydrocephalous and increased CSF cell count and protein level. Conclusion: Oculovisual anomalies formed an important group of clinical manifestations of bacterial meningitis. Incidence of oculovisual anomalies was more frequently seen in Tubercular meningitis (55%).Children with early presentation and intervention had better prognosis. Hence, timely intervention and health education is important. J. Nepal Paediatr. Soc. 32(2) 2012 136-141 doi: http://dx.doi.org/10.3126/jnps.v32i2.5534